2002
DOI: 10.1002/ptr.761
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and antipyretic effects of Myrica salicifolia (Myricaceae)

Abstract: Myrica salicifolia Hoechst (Myricaceae) root extract was found to have analgesic activity in mice. In rats there was antipyretic but no antiinflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Roots of medicinal plants are common ingredients of many folk and herbal medicines (Kweifio-Okai, 1991a,b;Hebtemariam, 2001) and root extracts of a number of medicinal plants have been reported to possess pharmacological activity, mainly anti-inflammatory activity (Basu and Chaudhuri, 1991;Sen and Nag Chaudhuri, 1991;Sen et al, 1993;Cuellar et al, 1997;Njung'e et al, 2002). Tea (Camellia sinensis), which is the most consumed beverage all over the world, has been reported to contain a number of chemical constituents possessing medicinal and pharmacological properties (Muramatsu et al, 1986;Toda et al, 1991;Blot et al, 1996;Arteel et al, 2002;Sartor et al, 2002) and it is expected that tea root might also be a storehouse of many chemicals of medicinal and pharmacological interest.…”
Section: Introductionmentioning
confidence: 99%
“…Roots of medicinal plants are common ingredients of many folk and herbal medicines (Kweifio-Okai, 1991a,b;Hebtemariam, 2001) and root extracts of a number of medicinal plants have been reported to possess pharmacological activity, mainly anti-inflammatory activity (Basu and Chaudhuri, 1991;Sen and Nag Chaudhuri, 1991;Sen et al, 1993;Cuellar et al, 1997;Njung'e et al, 2002). Tea (Camellia sinensis), which is the most consumed beverage all over the world, has been reported to contain a number of chemical constituents possessing medicinal and pharmacological properties (Muramatsu et al, 1986;Toda et al, 1991;Blot et al, 1996;Arteel et al, 2002;Sartor et al, 2002) and it is expected that tea root might also be a storehouse of many chemicals of medicinal and pharmacological interest.…”
Section: Introductionmentioning
confidence: 99%
“…The Myrica salicifolia plant has several pharmacological effects including: antibiotic, antiviral, antimalaria, analgesic, anticoagulant, anti hypertensive. The extracts of the roots of Myrica salicifolia have an analgesic effect in mice and they show an antipyretic effect in rats but no anti activityinflammatory [9], the Myrica salicifolia Hochst plant, ex. A.…”
Section: Introductionmentioning
confidence: 99%
“…Biological activity studies on M. salicifolia showed that methanolic extract of M. salicifolia stem bark was effective against Bacillus cereus, Neisseria gonorrhoeae, Shigella dysenteriae, and Staphylococcus aureus [23,24]. Additionally in vivo testing of a methanolic extract of this species in mice showed potent analgesic and antipyretic activity [25].…”
Section: Introductionmentioning
confidence: 99%